Turning one into five: Integrative taxonomy uncovers complex evolution of cryptic species in the harvester ant Messor “structor” - Steiner, Florian M.; Csősz, Sándor; Markó, Bálint; Gamisch, Alexander; Rinnhofer, Lukas; Folterbauer, Clemens; Hammerle, Sarina; Stauffer, Christian; Arthofer, Wolfgang; Schlick-Steiner, Birgit C. (Soil Organisms, 2018)

Description of Plagiolepis perperamus, a new species from east-Mediterranean and redescription of Plagiolepis pallescens Forel, 1889 (Hymenoptera: Formicidae) - Salata, Sebastian; Borowiec, Lech; Radchenko, Alexander G (Annales Zoologici (Warszawa), 2018)
A taxon considered in past years as P. pallescens sensu Radchenko is described as a new species: Plagiolepis perperamus sp. nov. based on material from Eastern Mediterranean. Its morphological separation from P. schmitzii Forel, 1895, the second species characterized by dense gaster setosity, is supported by study on their environmental niches. Plagiolepis pallescens Forel, 1889 is redescribed based on type specimens and material collected from various localities spread within Balkans. Its taxonomical status is clarified and a definition of a ‘pallescens group’ is improved and supplemented. Plagiolepis maura var. taurica Santschi, 1920 and Plagiolepis maura var. ancyrensis Santschi, 1920 are synonymized with Plagiolepis pallescens Forel, 1889.
Keywords: Ecological Niche Modelling INTRODUCTION; Formicidae; Formicinae; Mediterranean Region; Plagiolepidini

Three Turano-European species of the Temnothorax interruptus group (Hymeno ptera: Formicidae) demonstrated by quantitative morphology - Csősz, Sándor; Salata, Sebastian; Borowiec, Lech (Myrmecological News, 2018)
Keywords: Morphometrics; species delimitation; exploratory analyses; gap statistic; biogeography; new species